Grevillea pteridifolia - a New Introduction to Mined out Areas of Madhya Pradesh-II - Prasad, Ram; Chadhar, S. K. (Indian Forester, 1987)
An exotie from Australia Grevillea Pteridifolia has been found very successful on the bauxite and coal-mined out sites of Madhya Pradesh. The biomass production efficiency of this species has been found comparable to many other species (E camaldulensis and P. carihaea). An experiment was conducted on the bauxite mined out site at Amarkantak (Shahdol District) to determine the initial input requirements of Grevillea Pteridifolia. It has been observed that the species is very hardy and well adopted to orphaned sites as are available after mining or bauxite ore. The details of the experiment and its result have been discussed in this paper.